The Influence of Muhammadiyah University Surakarta's Tagline on Audience Brand Awareness and Campus Image - Rachmawati, Amanda Tri; Santoso, Budi (Universitas Syiah Kuala, 2025)
Competition among universities requires each institution to establish a strong identity that is easily recognizable and has a clear position in the public mind. One communication strategy used is the use of taglines as a representation of the institution's values and character. This study aims to analyze the influence of the tagline of Muhammadiyah University Surakarta (UMS), namely